Diarchic Hospitality: Richard Kearney on Arche and Otherness - Stephen Rehmalem Eliata (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2026)
Hospitality is a theoretical concept that underlies intersubjectivity, that is, my acceptance of the coming of strangers. Derrida and Caputo propose the concept of anarchy hospitality as the most radical form of hospitality, where hospitality occurs without a source/principle because the I fully welcomes the other. However, Kearney criticizes this thought because it actually creates a space for violence. The problem of an-archic radical hospitality lies in the asymmetrical relation between the I and the Other. Kearney's critique leads to the question of what the source/principle (arche) of radical hospitality is. In this paper, I argue that Kearney's concept of hospitality can produce radical hospitality through two arches: the necessary existence of the I and the other. Radical hospitality is hospitality in a symmetrical relational structure. As a competing concept of anarchy hospitality from Derrida and Caputo, I will call this hospitality model as di-archic hospitality. To prove my point, this study employs a qualitative methodology that integrates meta-analysis with conceptual analysis. First step, I will explain Kearney's thoughts on otherness. Secondly, I will explain Kearney's thoughts on arche. Finally, I will draw conclusions from the study that has been conducted.